Venezuelan migration in Brazil: A study of the humanitarian response for livelihoods - McGill, Dalia Carolyn Worcman (2024)
The surge in global migration in recent years has led to significant challenges for countries and humanitarian organizations worldwide. One of the largest groups affected by this phenomenon are Venezuelans, who have left their country due to a combination of economic, political, and social factors. Brazil, in particular, has experienced a substantial influx of Venezuelan migrants and refugees, with over 510,100 individuals arriving within its borders by November 2023. In response to this crisis, the Brazilian government launched Operação Acolhida (Operation Welcome), to address the needs of the migrant and refugee population. This research project focuses on analyzing the humanitarian response to the Venezuelan migration crisis in Brazil, with a specific emphasis on the interiorization strategy aimed at supporting migrants\' and refugees\' livelihoods. Through a qualitative case study approach, the study aims to achieve several objectives: gain insights into the lived experiences of migrants and humanitarian aid workers who have direct experience with the interiorization program, analyze the interiorization program and evaluate its success, and provide recommendations for improvement of the program. Findings from this research contribute to a better understanding of the complexities surrounding migration crises and humanitarian responses, particularly in the context of South America, providing insights to policy-makers. Additionally, the study offers recommendations for enhancing the effectiveness and inclusivity of humanitarian interventions, ultimately aiming to empower Venezuelan migrants and promote their integration into Brazilian society.